Enterococci isolated from Uruguayan Colonia cheese – occurrence and antimicrobial resistance. - González, Marcela; Olivera Rodi, Jorge; Amaro, Estefania; Reginensi, Stella (Journal of BioScience and Biotechnology, 2024)
In recent years, there is a growing concern for antibiotic resistance of food-related enterococci. This study aims to provide data for occurrence and antimicrobial resistance of Enterococcus spp. isolated from Colonia cheese. The results showed that Enterococcus spp. were found in two thirds of the cheese samples (47 out of 70), of which 72% were identified as E. faecalis, 16% as E. faecium, 6% as E. mundtii, 4% as E. hirae and 2% as E. durans. The antimicrobial suceptibility showed that almost all Enterococcus spp. were sensible to ampicillin and gentamicin. The highest incidence of resistance was displayed against erythromycin, tetracycline, rifampicin and fosfomycin. E. faecalis isolates presented high percentages of resistance to high level streptomycin. The multiple antibiotic resistance index was elevated in half of the Enterococcus spp., reaching values as high as 0,8, indicating a potential risk for public health. In this research, several Enterococcus isolates could be considered as multidrug-resistant, most of them belonging to E. faecalis. Results of present study raise concerns about possible role of cheese enterococci as reservoirs of antibiotic resistance.